2010
DOI: 10.4315/0362-028x-73.10.1780
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella in Raw Meat and By-Products from Pork and Beef

Abstract: After campylobacteriosis, salmonellosis is the second main cause of human bacterial enteritis in Germany. Salmonella is known to colonize the gastrointestinal tract of animals without producing any clinical signs. Therefore, carcasses can become contaminated with Salmonella at the time of slaughter. During an 11-month period, a total of 4,170 raw meat samples and by-products from beef and pork, obtained from seven different slaughterhouses in Southern Germany, were screened by the VIDAS system for Salmonella i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 22 publications
1
19
0
2
Order By: Relevance
“…The occurrence of false positive results may depend on the specificity of the antibody, which may present cross-reactions with correlated antigens. However, a recent report on the use of VIDAS ® for screening raw meat and by-products from pork and beef showed that the number of positive samples detected was two-fold higher than that by culture method (Meyer, Thiel, Ullrich, & Stolle, 2010).…”
Section: Resultsmentioning
confidence: 96%
“…The occurrence of false positive results may depend on the specificity of the antibody, which may present cross-reactions with correlated antigens. However, a recent report on the use of VIDAS ® for screening raw meat and by-products from pork and beef showed that the number of positive samples detected was two-fold higher than that by culture method (Meyer, Thiel, Ullrich, & Stolle, 2010).…”
Section: Resultsmentioning
confidence: 96%
“…in food products, including beef, chicken, pork and their by products, seafood, eggs, dairy products, fresh produce, chocolate, breakfast cereals, snacks and almonds, peanut butter, infant formula, and pet treats (Beuchat & Mann, 2010;Guan, Chen, & Hoover, 2005;Jin et al, 2008;Mahmoud, 2009Mahmoud, , 2010aMahmoud, , 2010bMahmoud, Vaidya, Corvalan, & Linton, 2008;Meyer, Thiel, Ullrich, & Stolle, 2010;Patel et al, 2010;Podolak, Enache, Stone, Black, & Elliott, 2010). The wide variety of products shows that Salmonella is able to grow and survive in a large range of conditions even low moisture and thermal processing.…”
Section: Salmonellamentioning
confidence: 99%
“…In April 2008 an outbreak related with Salmonella enterica serotype Saintpaul generated more than 1400 sick cases thorough the United States and Canada; the source was contaminated tomato, serrano and jalapeño peppers imported from Mexico (Klontz, Klontz, Mody, & Hoekstra, 2010). In other countries such as Germany, The Netherlands, Denmark, Finland and Sweden, Salmonella has also been either the main confirmed or suspected etiologic agent related with food-borne diseases (Meyer et al, 2010;Zhao, Zhao, & Doyle, 2010). Therefore, effective Salmonella inactivation in foods using any food processing technology is an urgent need to warrant consumers' safety.…”
Section: Salmonellamentioning
confidence: 99%
“…Evaluation of the VIDAS kit indicated that sensitivity of the assay could be reduced by the presence of competing microflora such as Citrobacter in the food matrices (Keith, 1997). On the other hand, a recent report on the use of VIDAS for screening raw meat and by-products from pork and beef showed that the number of positive samples detected was two-fold higher than that by culture method (Meyer, Thiel, Ullrich, & Stolle, 2010).…”
Section: Detection Of Salmonella In Food Samples By Immunoassay-basedmentioning
confidence: 99%